Efektivitas Kepemimpinan Transformasional Terhadap Peningkatan Kinerja Perawat - Fitriyanti Patarru'; Nursalam Nursalam; Eka Mishbahatul Mar’ah HAS (FORIKES, 2020)
Background: Transformational leadership is a style of leadership that motivates subordinates to work towards organizational goals. Objective: To determine the effectiveness of transformational leadership on nurse performance. Method: The database used in this study were Scopus, SAGE and Pubmed were limited to the last 5 years of publication from 2016 to 2020, full-text articles and in English. The keyword used were